Cryopreservation Effect on Structural-Functional Characteristics of Ehrlich Carcinoma Cells - Diabina, Olga A.; Ostankov, Maksim V.; Bondarovich, Nikolay A.; Goltsev, Anatoliy N. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Â Probl Cryobiol Cryomed 2014; 24(2):163.